Teaching competencies according to The TPACK model for chemistry teachers in Iraq - Hussain, Hawraa Oudah; Ahmed, Basma Mohammed; Ayash, Laith Mohammed (International Journal of Innovative Research and Scientific Studies, 2025)
The research aims to identify the degree of availability of teaching competencies according to the TPACK model among chemistry teachers in secondary schools in Iraq. The study used a descriptive correlational research method, with 300 teachers from day and evening secondary schools in Baghdad Al-Rusafa Governorate selected randomly for the 2022-2023 academic year. The TPACK model was used to assess teaching competencies, which consisted of 45 items across seven domains: content knowledge, educational knowledge, technological knowledge, content and educational knowledge, technology and content knowledge, technology and educational knowledge, and technology, education, and content knowledge. The results of the research showed that there is a weakness in the degree of availability of teaching competencies according to the TPACK model among chemistry teachers. The questionnaire as a whole indicated this, as shown by the results. The study found a lack of availability in areas of teaching competencies such as educational knowledge, technological knowledge, knowledge of technology and content, and knowledge of technology and education. However, the field of content knowledge was available. The researchers recommended in-service teacher training programs to integrate technology, education, and content knowledge.